Teacher Strategy in Character Education Independence of Class V Students Through Thematic Learning Activities - Pribadi, Raisya Alnadia; Suparno, Suparno; Hosnan, Hosnan (Jurnal Primagraha, 2020)
This study aims at describing the strategy of teachers the independent character education in elementary school 16 serang city. The subjects were teachers and students. Objects in this research that are independent of character education. This research is a qualitative descriptive study. Data collection procedures in this study were interviews, observation and documentation. Analysis of data using analysis techniques of data reduction, data display and conclusions. Checking the validity of the data using triangulation, in particular methodological triangulation. The results showed that the independent character in the school could be seen in some aspects of self-development, integration of different character values in the learning implementation plan, and school culture. Aspects of self- development consists of routine, spontaneous activity, programmatic activities and exemplary. Aspects of the integration of independent character value in the learning implemrntation plan consists of independent character value in education, put the value of independent character in the learning implementation plan, using contextual learning strategies, problem-based and cooperative. Aspects of school culture consists of the creation of conditions conducive school, curricular and extracurricular activities.